PERAN KURIKULUM, MASYARAKAT, DAN SUMBER DAYA DALAM KEBERHASILAN PENDIDIKAN - Husnul Hotimah, Ana; Ashari , Adelia; Arta Uli S, Romida; Muspawi, Mohamad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the role of curriculum, community, and educational resources in the success of education through a literature review approach. The research explores how these components interact to influence educational outcomes. Data were collected from relevant academic sources and were analyzed thematically. The findings indicate that the curriculum serves as the main guideline directing the learning process, while the community acts as a learning environment and educational partner that enhances contextual relevance and character development. In addition, human, physical, and non-physical resources are essential in supporting effective curriculum implementation. The study concludes that the integration of these three components is crucial in achieving quality and sustainable education.